2017
DOI: 10.1111/1556-4029.13361
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Rates of Ancestry Estimation by Forensic Anthropologists Using Identified Forensic Cases

Abstract: A common task in forensic anthropology involves the estimation of the ancestry of a decedent by comparing their skeletal morphology and measurements to skeletons of individuals from known geographic groups. However, the accuracy rates of ancestry estimation methods in actual forensic casework have rarely been studied. This article uses 99 forensic cases with identified skeletal remains to develop accuracy rates for ancestry estimations conducted by forensic anthropologists. The overall rate of correct ancestry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 27 publications
4
29
4
Order By: Relevance
“…3.2 | Does ancestry estimation really "work"? Thomas et al (2017) tout ancestry estimation success based on their comparison of identified cases to the corresponding forensic anthropological analyses. However, arguments such as this use circular logic because positively identified cases are known.…”
Section: Identity and Identificationmentioning
confidence: 99%
“…3.2 | Does ancestry estimation really "work"? Thomas et al (2017) tout ancestry estimation success based on their comparison of identified cases to the corresponding forensic anthropological analyses. However, arguments such as this use circular logic because positively identified cases are known.…”
Section: Identity and Identificationmentioning
confidence: 99%
“…We utilized the Freeman-Halton extension of Fisher's exact test to assess whether accuracy results were statistically significantly different for different variables [23,24]. This protocol generally followed Thomas et al [17] in order to enable direct comparisons between the two studies. However, the first variable examined in the FBI study, educational level of the analyst, was not available in the FADAMA dataset.…”
Section: Me Thodsmentioning
confidence: 99%
“…However, differences in accuracy among the groups were not statistically significant (p = 0.113-0.161). When accuracies were assessed by estimated ancestry, in order to assess whether certain ancestries were more likely to be incorrectly classified, all ancestries were a Please note that in this and the following tables, we chose to present group names alphabetically rather than following the presentation of Thomas et al [17] While following [17] would have maximized comparability of our data with the FBI data, we wished to eschew an arrangement which seems to list "White/European" first by default.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the same morphological features could also be used to classify groups defined by language, nationality, or time period because those are all features that structure populations [9][10][11][12]. Research has assessed accuracy rates of ancestry estimations by forensic anthropologists and reported correct ancestry estimates at 90.9% [13]. Contra to Bethard and DiGangi, these results highlight the strong concordance between genomic ancestry and self-reported race/ethnicity in the United States [14][15][16].…”
mentioning
confidence: 96%